Paleomagnetism, magnetic anisotropy and U-Pb baddeleyite geochronology of the early Neoproterozoic Blekinge-Dalarna dolerite dykes, Sweden - Gong, Zheng; Evans, David A. D.; Elming, Sten-Åke; Söderlund, Ulf; Salminen, Johanna M. (Precambrian Research, 2021)
Peer reviewed